Giant Primary Retroperitoneal Teratoma in an Adult: A Case Report - Poonam Mathur; Miguel A. Lopez-Viego; Myron Howell (Case Reports in Medicine)
Teratomas are bizarre neoplasms derived from embryonic tissues that are typically found only in the gonadal and sacrococcygeal regions of adults. Retroperitoneal teratomas are rare and present challenging management options. We report here the case of a histologically unusual retroperitoneal tumor detected on computed tomography during the workup of abdominal pain in a 32-year-old male. The evaluation and treatment of this condition and a review of the literature are included in this paper.